2017
DOI: 10.1371/journal.pntd.0005441
|View full text |Cite
|
Sign up to set email alerts
|

LigB subunit vaccine confers sterile immunity against challenge in the hamster model of leptospirosis

Abstract: Neglected tropical diseases, including zoonoses such as leptospirosis, have a major impact on rural and poor urban communities, particularly in developing countries. This has led to major investment in antipoverty vaccines that focus on diseases that influence public health and thereby productivity. While the true, global, impact of leptospirosis is unknown due to the lack of adequate laboratory diagnosis, the WHO estimates that incidence has doubled over the last 15 years to over 1 million cases that require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 55 publications
1
66
0
3
Order By: Relevance
“…Given the limitations of the whole-cell vaccines currently in use, identifying the perfect protein candidate has been a major effort in the field of vaccine development for leptospirosis 3 . Immunization with Lig proteins or LipL32 2,38,39 has been shown to confer protection, albeit not cross-protective immunity, against experimental infection. However, efficacy results have been proven difficult to replicate 2,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the limitations of the whole-cell vaccines currently in use, identifying the perfect protein candidate has been a major effort in the field of vaccine development for leptospirosis 3 . Immunization with Lig proteins or LipL32 2,38,39 has been shown to confer protection, albeit not cross-protective immunity, against experimental infection. However, efficacy results have been proven difficult to replicate 2,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The two vaccine strategies have shown decline of agglutinin titers at the day 60 of the experiment thought the test fish in aquaria being normal till termination of experiment. This may be due to the phenomenon of sterile immunity , Table 6, were the antibody prevents pathogens from expressing their pathological effect [24,25],decline effector and/ or memory B cell functions or due the interplay of cellular immune factors in immune efficacy of these vaccine strategies. Though the latter possibility is far from being the case.…”
Section: Discussionmentioning
confidence: 99%
“…While these results suggest a possible link between domain stability and protection consistency, leptospirosis challenge experiments have many notable issues, including the animal model (Gomes‐Solecki, Santecchia, & Werts, ), the challenge strain (Fouts et al, ), the delivery method (Coutinho et al, ), and the use of adjuvants, that can each cause variability between vaccine trials (Vernel‐Pauillac & Werts, ). Comparing two recent LigB studies that used different adjuvants, the trial that incorporated the potent Alum adjuvant provided sterilizing immunity (Conrad et al, ), whereas the other trial used mycobacterial‐derived Freund adjuvant and did not provide complete protection (Evangelista et al, ). The best adjuvants should improve immune response kinetics thereby reducing the importance of antigen stability (Liang & Lore, ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous Lig protein studies should be considered in the context of domain thermostability. Vaccine trials utilizing recombinant Lig protein‐based antigens have shown results ranging from sterile immunity to only partial protection (Adler, ; Cao et al, ; Conrad et al, ; Evangelista et al, ; Yan et al, ). Variable handling and storage procedures could easily affect vaccine trial outcomes with a bias against domains with poor thermostability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation